The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15294/jpii.v9i4.25332
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Students’ Metacognition and Digital Literacy in Virtual Lectures during the Covid-19 Pandemic on Achievement in the “Methods and Strategies on Physics Learning” Course

Abstract: This study aims to determine the effect of students’ metacognition and digital literacy skills on virtual lectures in the COVID-19 pandemic on achievement in the “Methods and Strategy on Physic Learning (MSPL)” course. The data was collected using a survey method which involved all 42 physics education students. The data analysis was carried out in two stages, namely the categorization stage and the correlation stage. Based on the data and analysis, it is known that the metacognition skill of physics edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…Digital learning using the Algodoo application gives students the opportunity to explore physics learning materials for free and able to attract students' attention Sukarno & Widdah, M.E. [30] 0,49 (Q2) 1…”
Section: Literature Review Of Digital Learning Tomentioning
confidence: 99%
“…Digital learning using the Algodoo application gives students the opportunity to explore physics learning materials for free and able to attract students' attention Sukarno & Widdah, M.E. [30] 0,49 (Q2) 1…”
Section: Literature Review Of Digital Learning Tomentioning
confidence: 99%
“…Designing educational activities according to levels of meta-cognitive thinking is one of the learning requirements in the era of Covid-19, as the learner during the pandemic bears a great deal of responsibility for his learning, as he must be involved in the planning, control, and assessment of his learning [25]. This is consistent with the results of some previous studies that demonstrated the importance of planning educational technologies and activities according to meta-cognitive thinking models that can prepare the learner to engage in learning processes and events.…”
Section: Meta-cognitive Thinkingmentioning
confidence: 99%
“…Although the gamification system is based mainly on external digital incentives, which sometimes have a negative impact on intrinsic motivation, people who perform activities because of extrinsic motivation are often less willing to carry out learning tasks and activities when such motivations are removed [49][50][51], however, some of the scientific studies that aimed to carry out comparisons between several performances that are linked to extrinsic incentives and those performed without incentives showed that groups whose members receive incentives have better effectiveness in performance and implementation of tasks, as indicated by Wise and DeMars [52], which examined (12) various studies aimed at conducting (25) comparisons between performance with incentive and performance without incentives, and the result showed an effect of (0.6) in favor of the groups that received additional external incentives.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a global scope, through the United Nations, a meeting was held to discuss literacy intelligence along with the importance of literacy for the community or students in facing the rapid development of Information Technology (Harmoko, 2021) . The efforts made by Indonesia in the literacy program continue to be promoted until this program can be implemented in accordance with the flow and rules that can be implemented and applied in the world of education or society so that it can provide benefits for change and renewal of life evenly (Sukarno & Widdah, 2020) . Meanwhile, Indonesia has made efforts to develop a literacy movement that is formed for the whole community with a view to accelerating the process of literacy culture along with the implementation of literacy is still low and far from the average international standard.…”
Section: Theoretical Reviewmentioning
confidence: 99%